Antiviral Effect of Propylene Glycol against Envelope Viruses in Spray and Volatilized Forms - Yui Hirama; Shintaro Onishi; Ryunosuke Shibata; Hirohiko Ishida; Takuya Mori; Noriyasu Ota (Viruses, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is highly contagious and continues to spread worldwide. To avoid the spread of infection, it is important to control its transmission routes. However, as methods to prevent airborne infections are lacking, people are forced to take measures such as keeping distance from others or wearing masks. Here, we evaluate the antiviral activity of propylene glycol (PG), which is safe, odorless, and volatile. PG showed pronounced antiviral activity against the influenza virus (IAV) at concentrations above 55% in the liquid phase. Given its IAV inactivation mechanism, which involves increasing the fluidity of the viral membrane, PG is expected to have a broad effect on enveloped viruses. PG showed antiviral activity against SARS-CoV-2. We also developed a system to evaluate the antiviral effect of PG in spray and volatilized forms. PG was found to be effective against aerosol IAV in both forms; the effective PG concentration against IAV in the vapor phase was 87 ppmv (0.27 mg/L). These results demonstrate that PG is an effective means for viral inactivation in various situations for infection control. This technology is expected to control the spread of current and future infectious diseases capable of causing outbreaks and pandemics.